Sinking the Internet: Pricing, Sunk Costs, and Market Structure Online. - Latcovich, S; Smith, H (Department of Economics (University of Oxford), 2000)
This paper evaluates alternative strategic models of competition and market structure in online retailing, and makes comparisons with traditional retailing. Online consumers are less concerned than traditional consumers about spatial characteristics and more concerned about hidden quality characteristics. Online retailers rely more on advertising than traditional retailers do, to inform consumers and to signal hidden quality attributes. Price competition may be imperfect, because of vertical product differentiation, incomplete consumer awareness, and perfect information exchange between retailers. Advertising and revenue data for the online book market reveal that consumers respond to advertising rather than low prices. As the market increases, advertising costs escalate and there is no new entry. Advertising to sales ratios and market concentration ratios are much higher than for traditional retailers. Using price and demand information for individual books over a number of weeks, we find counter-cyclical and cross-sectional price variation inconsistent with perfect price competition.